THE INFLUENCE OF INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE AND COMPANY VALUE IN INDONESIA - Elwisam; Suadi Sapta Putra; Herry Krisnandi; Kumba Digdowiseiso; Jumadil Saputra (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
Human resources is a crucial asset in a company's operations. Intellectual capital refers to the intangible assets that exert control over a company's other resources. The caliber of a company's intellectual capital can impact its performance, which can be assessed by analyzing its financial performance and overall value. In light of the significant impact of intellectual capital on financial performance and company valuation in Indonesia, there is a pressing need for more focused and specific studies on this subject. Hence, the objective of this study is to elucidate the impact of intellectual capital on the financial performance and company value in Indonesia through the utilization of the literature review methodology. The employed approach entails a systematic literature review comprising four distinct stages: identification, screening, feasibility assessment, and inclusion. Between 2017 and 2023, a total of 99 literary works were identified that discuss topics with citations dating back to 1926. The sectors examined encompass the chemical industry, food and beverage, manufacturing, banking subsector, advertising, printing, and media, mining, automotive, as well as property and real estate. The presence of intellectual capital exerts a significant impact on the majority of these sectors. This impact is further reinforced by various other factors, including effective corporate governance, profitability, and company leverage.